Recorded and Unrecorded Lac-hosts from West Bengal - DasGupta, J. M.; Mehra, B. P. (Indian Forester, 1967)
The authors record 28 lac-hosts from West Bengal including 15 hosts recorded by previous authors, 4 of which have also been observed by the present authors. The remaining 13 hosts have been recorded by the present authors, 2 of which are new and 11 first records from this State.